2007
DOI: 10.1039/b701661a
|View full text |Cite
|
Sign up to set email alerts
|

A concise first total synthesis of narceine imide

Abstract: A concise and efficient total synthesis of alkaloid narceine imide is disclosed. The key steps are based upon the sequential construction of the isoindolinone template followed by metalation and coupling with an isoquinolinium salt. Subsequent E1cb elimination enables the creation of the arylmethylene unit with the concomitant formation of the dimethylaminoethyl chain and ultimate deprotection completes the synthesis of the natural product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…Despite detailed investigation on the possible mechanism involved in this transformation (theoretical calculations at DFT level), the authors were unable to rationalize the stereochemical reversal observed with this reaction with respect to the normal behavior of similar VMMnR involving silyloxy furan analogues. 290 as the key transformation in a short total synthesis of narceine imide 704, a strong inhibitor of aldehyde reductase and liver alcohol dehydrogenase. In the event (Scheme 127), dimethoxy-isoindolinone 701 was reacted with N-methyl-dihydroisoquinolinium iodide 702 in the presence of KHMDS in THF at -78°C to afford racemic adduct (()-703, which was isolated as a 1:1 mixture of diastereoisomers.…”
Section: Scheme 124 Auxiliary-driven Diastereoselective Vmmnr Employmentioning
confidence: 99%
“…Despite detailed investigation on the possible mechanism involved in this transformation (theoretical calculations at DFT level), the authors were unable to rationalize the stereochemical reversal observed with this reaction with respect to the normal behavior of similar VMMnR involving silyloxy furan analogues. 290 as the key transformation in a short total synthesis of narceine imide 704, a strong inhibitor of aldehyde reductase and liver alcohol dehydrogenase. In the event (Scheme 127), dimethoxy-isoindolinone 701 was reacted with N-methyl-dihydroisoquinolinium iodide 702 in the presence of KHMDS in THF at -78°C to afford racemic adduct (()-703, which was isolated as a 1:1 mixture of diastereoisomers.…”
Section: Scheme 124 Auxiliary-driven Diastereoselective Vmmnr Employmentioning
confidence: 99%
“…[27] The palladacycle was tested with the various ligands (Table 3, entries 5-9), and the best yield was obtained with [(tBu) 3 PH]BF 4 (61 %; Table 3, entry 9). This led us to use Herrmann's palladacycle as the palladium source to promote the reactions.…”
Section: Optimization For Aryl Bromidesmentioning
confidence: 99%
“…This led us to use Herrmann's palladacycle as the palladium source to promote the reactions. The highest yield of 3a was obtained using Herrmann's palladacycle (5 mol-%) and [(tBu) 3 PH]BF 4 (10 mol-%) after 30 min of microwave irradiation at 120°C, with DBU as the base (74 %; Table 3, entry 10). In an attempt to further improve the yield, the reaction was tested in the presence of a base, e.g., DBU, Et 3 N, or K 2 CO 3 (Table 3, entries 10, 12, and 13, respectively).…”
Section: Optimization For Aryl Bromidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Isoindolinones and pyrrolones are the core structures of numerous natural alkaloids [2527] as well as many drug candidates [2830]. Isoindolinones demonstrate a remarkably wide range of biological activities, including anti-inflammatory, antihypertensive, antipsychotic and antileukemic and antiviral effects [3133].…”
Section: Introductionmentioning
confidence: 99%